An EOQ model for deteriorating items when demand is cloud fuzzy. Issue 1 (17th June 2022) - Shah, Nita H.; Patel, Milan
In this study, an EOQ model with constant rate of deterioration is developed and solved in crisp, fuzzy and cloud fuzzy environment. Demand is considered as a normal triangular fuzzy number and cloud normal triangular fuzzy number in uncertain environments to get the total minimum inventory cost. Yager's ranking index is used for defuzzification. The objective is to minimise the total inventory cost and compare the results in crisp, fuzzy and cloud fuzzy environment. With the help of numerical example, it is observed that the cloud fuzzy environment produce better results. Sensitivity analysis has also been performed to understand the change in optimal solution as various parameters changes.